2014
DOI: 10.1021/jp4125205
|View full text |Cite
|
Sign up to set email alerts
|

Polarity Controlled Reaction Path and Kinetics of Thermal Cis-to-Trans Isomerization of 4-Aminoazobenzene

Abstract: Spectral and kinetic behavior of thermal cis-to-trans isomerization of 4-aminoazobenzene (AAB) is examined in various solvents of different polarities. In contrast to azobenzene (AB), it is found the rate of thermal isomerization of AAB is highly dependent on solvent polarity. Accelerated rates are observed in polar solvents as compared to nonpolar solvents. Moreover, a decrease in the barrier height with an increase in medium polarity is observed. Our observations suggest that inversion is the preferred pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 55 publications
6
37
0
1
Order By: Relevance
“…Azobenzenes are common organic dyes that have been extensively studied both experimentally and theoretically owing to their potential applications in material science, medicinal chemistry, molecular switches and other devices [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. They are photo-reactive molecules that undergo reversible photo-isomerization from the more stable trans-isomer to the less stable cis-isomer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Azobenzenes are common organic dyes that have been extensively studied both experimentally and theoretically owing to their potential applications in material science, medicinal chemistry, molecular switches and other devices [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. They are photo-reactive molecules that undergo reversible photo-isomerization from the more stable trans-isomer to the less stable cis-isomer.…”
Section: Introductionmentioning
confidence: 99%
“…In all cases, the rate of isomerization increases as the solvent polarity increases with a concomitant decrease in the activation energy, enthalpy, entropy and free energy of activation for the cis-trans isomerization process (Tables 1 and 2) [20,23].…”
mentioning
confidence: 98%
“…Thus, the gap of the reaction enthalpy of the two isomers with CO 2 remains, more or less, constant in different solvents. Wada and co‐workers recently reported on 4‐aminoazobenzene, and the almost identical and limited sensitivity toward solvents are attributed to the isomers′ close and relatively small dipole moments 41…”
Section: Resultsmentioning
confidence: 82%
“…Moreover, inversion is the preferred pathway in cis-trans thermal isomerization in a nonpolar medium; but, under polar conditions, the isomerization adopted a rotational behavior. The same study concluded that kinetics and the mechanism of thermal isomerization is controlled by the polarity of the medium [42][43][44].…”
Section: Isomerization Of Schiff Basesmentioning
confidence: 99%